APLIKASI MOBILE KOMUNITAS GERAKAN BANTU SERIBU ANAK ASUH (GBSA) DENGAN CLIENT SERVER BERBASIS ANDROID - Amras Mauluddin; Uray Yufikar (LPPM STMIK Indonesia Mandiri, 2019)
Currently education and poverty is a problem as it gives an enormous impact on people's lives. As we can see, the number of school dropouts has increased every day. Seeing this condition, Gerakan Bantu Seribu Anak Asuh (GBSA) is present to participate to help children who are less fortunate, to be able to stay in school. Gerakan Bantu Seribu Anak Asuh (GBSA) is a social community that bridges donors and children who are less fortunate to get help. In reality this donation management faced several obstacles both in terms of data management to the confirmation process donations made by donors each donating. Therefore, by presenting the android-based mobile applications is expected to be a solution to help officers GBSA share information and manage the donations were mandated as well as for donors could further facilitate the process of sharing and confirmation. Applications software development methods that will be used the method of Rapid Application Development (RAD). This method is one method used to develop apalikasi android with short cycles thereby enabling much faster. After testing with a method black box can be concluded that the system is in conformity with the expected goals.